Differentially expressed small RNAs in arabidopsis galls formed by meloidogyne javanica: a functional role for miR390 and its TAS3-derived tasiRNAs - Cabrera, Javier; Barcala, Marta; Maizel, Alexis (The new phytologist, 2016)
Root-knot nematodes (RKNs) induce inside the vascular cylinder the giant cells (GCs) embedded in the galls. The distinctive gene repression in early-developing GCs could be facilitated by small RNAs (sRNA) such as miRNAs, and/or epigenetic mechanisms mediated by 24nt-sRNAs, rasiRNAs and 21-22nt-sRNAs. Therefore, the sRNA-population together with the role of the miR390/TAS3/ARFs module were studied during early gall/GC formation. Three sRNA libraries from 3-d-post-inoculation (dpi) galls induced by Meloidogyne javanica in Arabidopsis and three from uninfected root segments were sequenced following Illumina-Solexa technology. pMIR390a::GUS and pTAS3::GUS lines were assayed for nematode-dependent promoter activation. A sensor line indicative of TAS3-derived tasiRNAs binding to the ARF3 sequence (pARF3:ARF3-GUS) together with a tasiRNA-resistant ARF3 line (pARF3:ARF3m-GUS) were used for functional analysis. The sRNA population showed significant differences between galls and controls, with high validation rate and correspondence with their target expression: 21-nt sRNAs corresponding mainly to miRNAs were downregulated, whilst 24-nt-sRNAs from the rasiRNA family were mostly upregulated in galls. The promoters of MIR390a and TAS3, active in galls, and the pARF3:ARF3-GUS line, indicated a role of TAS3-derived-tasiRNAs in galls. The regulatory module miR390/TAS3 is necessary for proper gall formation possibly through auxin-responsive factors, and the abundance of 24-nt sRNAs (mostly rasiRNAs) constitutes a gall hallmark.